2013
DOI: 10.1159/000343912
|View full text |Cite
|
Sign up to set email alerts
|

A Similar but Distinctive Pattern of Impaired Cortical Excitability in First-Episode Schizophrenia and ADHD

Abstract: Background: First-episode schizophrenia (FE-SZ) and attention deficit hyperactivity disorder (ADHD) are both neuropsychiatric disorders associated with an impaired dopaminergic transmission. Though displaying different clinical phenotypes, a common pathophysiological pathway is discussed controversially. Several studies using transcranial magnetic stimulation (TMS) revealed abnormalities in human motor cortex excitability in both schizophrenia and ADHD patients. Studies on cortical excitability comparing these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 107 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…This is worthy of further investigation, as the results of the western blots, which were conducted separately for tissue from each hemisphere, indicated a selective left-sided effect. This may be relevant to schizophrenia as a number of studies 59 have suggested that alterations in hemispheric asymmetry, including in one example, selective reductions in inhibition in the left hemisphere, 60 may be important in the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This is worthy of further investigation, as the results of the western blots, which were conducted separately for tissue from each hemisphere, indicated a selective left-sided effect. This may be relevant to schizophrenia as a number of studies 59 have suggested that alterations in hemispheric asymmetry, including in one example, selective reductions in inhibition in the left hemisphere, 60 may be important in the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including ppTMS studies from 1990 to 2012 found no changes of ICF, but decreased short-interval intracortical inhibition, in schizophrenia (41). By contrast, later research with small sample sizes revealed significant increases of ICF in first-episode schizophrenia compared with healthy control subjects (42). In addition, I-wave facilitation was found to be increased in patients with schizophrenia (43).…”
Section: Introductionmentioning
confidence: 89%
“…SICI was not correlated with illness duration in patients with schizophrenia, 45,60 although those who had a relatively short duration of illness (e.g., less than 3 years) or treatment (i.e., not longer than 6 weeks continuously) also showed reduced SICI in the motor cortex compared to healthy controls. 46,60,174 Therefore, the decrease in SICI in schizophrenia may have been independent of illness and treatment duration.…”
Section: J Psychiatry Neurosci 2021;46(6)mentioning
confidence: 99%
“…43 TMS and other noninvasive stimulation techniques are used to elicit plastic changes in synaptic organization, interfering with the function of specific cortical areas by inducing long-term potentiation or long-term depression. [44][45][46][47] For example, transcranial direct current stimulation (tDCS) is a neuromodulation technique that induces changes in cortical excitability by applying a small current over the scalp. This technique modu lates the activity of spontaneous neurons by tonic depolarization (anodal tDCS) or hyperpolarization (cathodal tDCS) of their membrane, inducing long-lasting changes in neuronal firing rates.…”
Section: Introductionmentioning
confidence: 99%